Manhaj Ta’līm Mahārah Kalām Bi Al-Lughah Al-‘Arabiyah Baina al-Ma’had Al-Ashry Wa As-Salafy - Moh. Munir; Rizka Eliyana Maslihah (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2022)
Language becomes the main media in communication, through human language can establish relationships and reach understanding. The main sources of Islamic teaching are written in Arabic. Then, there are four skills in learning Arabic, one of them is speaking skills. Speaking Skill is a receptive ability, which requires the speaker must be able to speak the language using Nahwu's rules and language structure correctly. Modern Islamic Boarding School (IBS) is an educational institution that pays special attention to developing Arabic speaking skills. Besides that, the same special attention is become from Salafy IBS. The development is implemented through language activities curriculum, and the emphasis is on language environment. This article was written using the Qualitative Research approach with case study type, aimed at knowing the full description of the learning objectives, teaching materials, learning steps and evaluation rule that used of the language in both of these Islamic Boarding Schools. And the conclusion is: 1) The main purpose of learning speaking is to get students to speak fluently in Arabic with the correct rules. 2) Textbooks used specifically for teaching Arabic speaking. 3) The learning step uses a direct approach. 4) Language evaluation includes: Weekly, monthly, semester and yearly evaluations.